CLINICAL HETEROGENEITY OF EARLY PSORIATIC ARTHRITIS - V. V. Badokin; I. A. Troshkina (Современная ревматология, 2016)
Objective: to reveal the characteristic symptoms and syndromes of early-stage psoriatic arthritis (ePsA), which are pivotal to its early diagnosis.Patients and methods. Fifty-one patients with a PsA duration of less than 2 years (mean 12 months) were examined. The diagnosis of PsA was established on the basis of the conventional CASPAR criteria and the Russian criteria developed by the expert method. The conventional current criteria, including the number of tender and swollen joints, DAS28, values of acute-phase indicators, were used to detect inflammatory activity. Skin syndrome was evaluated using the Psoriasis Area and Severity Index (PASI). X-ray study of the hands, distal and proximal feet, pelvis, and other involved joints and MRI of the distal hands/feet were performed. The Maastricht Ankylosing Spondylitis Enthesitis Score (MASES) and reduced GUESS were used to assess enthesopathy.Results. The types of articular syndrome in ePsA were identified in accordance of the duration of the disease. The authors determined the characteristic features of arthritis, spondylitis, enthesitis, and dactylitis, their diagnostic value and associations with other manifestations in the first 2 years of PsA. There was a relationship of dermatitis and psoriatic onychopathy to the clinical picture of articular syndrome.Conclusion. ePsA is characterized by marked heterogeneity of articular syndrome with predominantly mono/oligoarthritic and polyarthritic articular syndrome. The significant signs are enthesitis and dactylitis, which serve as risk factors for the unfavorable course of the disease.